The Intrapreneur Identity Illusion: Unraveling the Identity Work of Intrapreneurs in Internal Corporate Venturing - Starmann, Frederic-Alexander; Tomin, Slawa; Hubner-Benz, Sylvia; Kabst, Rüdiger (Journal of Product Innovation Management)
ABSTRACT Intrapreneurs—employees participating in internal corporate venturing (ICV) programs—are vital in nurturing entrepreneurship within organizations. While existing literature has extensively studied ICV at the organizational level, research on individual‐level processes remains limited, particularly regarding intrapreneurs' identity‐related conflicts over time. However, to design programs and interventions that unlock employees' creative potential and promote innovation, it is crucial to understand these individual dynamics. We conducted an 18‐month longitudinal study of 21 intrapreneurs within an ICV program, developing a process model and theory of intrapreneurs' identity work. We find that aspiring intrapreneurs construct an “idealized entrepreneur identity” that fundamentally conflicts with their employee identity. To maintain a coherent sense of self, they either safeguard their emerging entrepreneur identity by denying corporate dependence and eventually opposing the organization or they realign with their employee role, forsaking their intrapreneurial aspirations. These findings challenge the implicit assumption of a distinct intrapreneur identity, demonstrating how and why intrapreneurs struggle to construct a coherent and positively valued identity as intrapreneurs. We term this phenomenon the intrapreneur identity illusion and highlight its detrimental effects for both individuals and organizations. Our research contributes to understanding the individual‐level foundations of corporate entrepreneurship and offers broader implications for innovation management.

Unveiling the Impact of Cultural Value Orientations on Ideation Outcomes: Evidence From the International #EUvsVirus Hackathon - Krebs, Benjamin P.; Funck, Marieke; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (R&D Management)
ABSTRACT This study addresses the role of national culture in shaping hackathon teams' ideation outcomes. Drawing on the innovation and creativity literature and Schwartz’ theory of cultural value orientations, we propose that hierarchical values decrease the quality of ideas that teams develop over the course of a hackathon and that intellectual autonomy and mastery improve it. Using archival data, including pitch presentations from an international hackathon and data on cultural value orientations, we compiled a sample of 308 teams to investigate the influence of cultural value orientations and employed linear mixed‐effects regression analysis to test our hypotheses. We found that hierarchical cultural values are negatively associated with the quality of ideas, which suggests that hackathon teams that operate in such cultures suffer from a “liability of hierarchy.” We also found that teams from societies that emphasize mastery of the natural and social environment are more likely than other teams are to develop high‐quality ideas to tackle the (grand) challenges that hackathons address. We found no relationship between intellectual autonomy and idea quality. The study findings support the notion that culture manifests in hackathon teams' behavior and so shapes the quality of ideas they develop, thus laying the foundation for success or failure.

The Equivocal Image of Young Social Enterprises - How Self- vs. Other-Oriented Values Influence External Perceptions - Yahyaoui, Y.; Jakob, E.A.; Steinmetz, Holger; Wehner, M.C.; Isidor, R.; Kabst, Rüdiger (Nonprofit Management & Leadership)

Erfolgreiches People Management in KMU und Start-ups - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Methodenverliebt am Markt vorbei? - Rebert, Tobias; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (Intrapreneurship)

Like It or not: When corporate social responsibility does not attract potential applicants - Jakob, Eva Alexandra; Steinmetz, Holger; Wehner, Marius; Engelhardt, Christina; Kabst, Rüdiger (Journal of Business Ethics)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

National culture and incentives: Are incentive practices always good? - Prince, Nicholas R.; Bruce Prince, J.; Kabst, Rüdiger (Journal of World Business)

Corporate Entrepreneurship: Die Rolle und Bedeutung des Humankapitals - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Corporate Entrepreneurship durch die Allokation von Ressourcen - Megow, N.; Kabst, Rüdiger (Perspektiven des Entrepreneurships: Unternehmerische Konzepte zwischen Theorie und Praxis)

The Other Side of the Same Coin – How Communal Beliefs About Entrepreneurship Influence Attitudes Toward Entrepreneurship - Jakob, Eva Alexandra; Isidor, Rodrigo; Holger, Steinmetz; Marius, Wehner; Kabst, Rüdiger (Journal of Vocational Behavior)

The Contextual Role of Regulatory Stakeholder Pressure in Proactive Environmental Strategies: An Empirical Test of Competing Theoretical Perspectives - Jakob, Eva Alexandra; Baum, Matthias; Huett, Pascal; Kabst, Rüdiger (Organization & Environment)

The Collaboration of Human Resource Management and Line Management–An International Comparison - Szierbowski-Seibel, Klaas; Wach, Bernhard A.; Kabst, Rüdiger (Organization Management Journal)

Impact of national culture on organizations’ use of selection practices - Prince, Nicholas Ryan; Kabst, Rüdiger (Employee Relations: The International Journal)
Purpose The purpose of this paper is to investigate the impact of national culture on organizations’ use of selection practices, specifically to investigate the impact of in-group collectivism, uncertainty avoidance and power distance on interview panels, one-on-one interviews, applications forms, references, ability, technical and psychometric tests. Design/methodology/approach This study uses survey data from the 2008–2010 CRANET database. It uses OLS regression analysis to test the impact of national culture on organizations’ use of selection practices. Findings In-group collectivism increases the use of panel interviews and technical tests, and decreases the use of one-on-one interviews and application forms. Uncertainty avoidance increases the use of panel interviews and technical tests, and a decrease in one-on-one interviews, applications ability, and psychometric tests. Power distance leads to an increase in one-on-one interviews, applications and ability tests, and a decrease in panel interviews, psychometric tests and references. Originality/value This paper investigates the use of the impact of national culture on selection practices. Specifically, it looks at the use of a large number of selection practices panel interviews, one-on-one interviews, applications and references, and several different tests, ability, technical and psychometric.

Corporate Entrepreneurship: HR als Treiber und Begleiter des Wandels - Krebs, Benjamin; Izsak, L.; Kabst, Rüdiger (PERSONALquartely)

The more the merrier? Immigrant share and entrepreneurial activities. - Li, C; Dau, L A; Kabst, Rüdiger (Entrepreneurship Theory and Practice.)

Age Diversity and team outcomes: A quantitative review. - Schneid, M; Isidor, R; Steinmetz, Holger; Kabst, Rüdiger (Journal of Managerial Psychology.)

The Impact of Structural and Attitudinal Antecedents on the Instability of International Joint Ventures: The Mediating Role of Asymmetrical Changes in Commitment. - Isidor, R; Schwens, C; Hornung, F; Kabst, Rüdiger (International Business Review (IBR).)

Der Einfluss bio-demographischer und fachlicher Diversität auf die Leistung von Teams: Eine Metaanalyse. - Schneid, M; Isidor, R; Schwens, C; Kabst, Rüdiger; Weber, I (Die Betriebswirtschaft.)